Integral terminal sliding mode-based adaptive driving control method of tracked robots - Li, Zhiqiang; Luo, Kun; Tao, Liang; Zhou, Yan (Frontiers in Plant Science, 2025)
Tracked robots (TR) exhibit significant advantages field applications due to their stability and adaptability to uneven and soft terrains. When the TR operating on soft or uneven terrain, the interaction between the tracks and the ground introduces disturbances, these disturbances leading to challenges in maintaining precise driving control. In this work, we address these issues by proposing an adaptive control strategy for tracked robots. First, the disturbance models are established based on the Bekker pressure-sinkage and Janosi shear theories, enabling a comprehensive understanding of the robot-terrain interaction dynamics. Subsequently, an adaptive integral terminal sliding mode (AITSM) control method is introduced to enhance the robustness and precision of the driving system under complex environmental conditions. Experimental results demonstrate the effectiveness and superior performance of the proposed method in real-world scenarios. This study not only provides a solution for improving the control of tracked robot in outdoor applications but also offers a framework for driving control in a wide range of intelligent field machinery, including agricultural robots, exploration vehicles, and disaster response systems.